Analysis of the Critical Thinking Initial Ability about Static Fluid Material in Class XI of SMA Negeri 7 Surakarta - Akhyani Nasution; Widha Sunarno; Sri Budiawanti (Future Science, 2020)
This research aims to describe the initial ability of critical thinking, of high school students in Surakarta on static fluid. This study is part of the learning tools development study to improve critical thinking ability. The critical thinking skills test is compiled into ten questions. The analyzed critical thinking skills are students' critical thinking abilities before a model is applied that is expected to develop a student's critical thinking skills. This research includes descriptive research. The subjects of this study were 35 students of Class XI in SMA Negeri 7 Surakarta. The data collection methods used are test methods. Data analysis techniques use quantitative descriptive analysis. The results showed that the achievement of critical thinking in the analysis aspect with sub-skills of detecting arguments and analyzing arguments was 41,75%. The inference aspect with sub-skills of making a logical conclusion was 29,25%. The interpretation aspect with sub-skills of classifying the meaning was 44,1 %. The explanation aspect with sub-skills of stating results, justifying procedures, and presenting arguments was 57,7%. And the evaluation aspect with sub-skills of assess the credibility and assess the quality of arguments was 24,65%. These results show that students' critical thinking skills are still low, especially in evaluation aspects.